2008
DOI: 10.1103/physrevlett.100.045503
|View full text |Cite
|
Sign up to set email alerts
|

Phase Stability and Pressure Dependence of Defect Formation inGd2Ti2O7andGd2Zr

Abstract: We report dramatically different behaviors between isostructural Gd2Ti2O7 and Gd2Zr2O7 pyrochlore at pressures up to 44 GPa, in which the substitution of Ti for Zr significantly increases structural stability. Upon release of pressure, the Gd2Ti2O7 becomes amorphous. In contrast, the high-pressure phase of Gd2Zr2O7 transforms to a disordered defect-fluorite structure. First-principle calculations for both compositions revealed that the response of pyrochlore to high pressure is controlled by the intrinsic ener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
92
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(103 citation statements)
references
References 30 publications
8
92
1
Order By: Relevance
“…It is found that the threshold displacement energies for both cations and anions in La 2 order-disorder transition to form a defect-fluorite structure. Since the defect-fluorite structure is extremely stable under ion-irradiation and structural amorphization cannot be induced, our calculations suggest that Nd 2 Zr 2 O 7 and Sm 2 Zr 2 O 7 are more radiation resistant than La 2 Zr 2 O 7 , which is in good agreement with the experiments.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…It is found that the threshold displacement energies for both cations and anions in La 2 order-disorder transition to form a defect-fluorite structure. Since the defect-fluorite structure is extremely stable under ion-irradiation and structural amorphization cannot be induced, our calculations suggest that Nd 2 Zr 2 O 7 and Sm 2 Zr 2 O 7 are more radiation resistant than La 2 Zr 2 O 7 , which is in good agreement with the experiments.…”
Section: Discussionmentioning
confidence: 97%
“…Zirconate pyrochlores, with the chemical formula A 2 Zr 2 O 7 (where A is a rare earth element), have attracted considerable attention because of their potential use as solid oxide fuel cell electrode materials, fluorescence screens, thermal-barrier coatings, high-temperature heating elements, oxidation catalysts, and refractory ceramic materials for use in magnetohydrodynamic power generation [1][2][3][4][5][6][7][8]. Because they exhibit remarkable resistance to structural amorphization under ion-beam irradiation [6] and high chemical durability (release rates typically <10 À5 g m À2 d À1 based on zirconium) [9], as well as the fact that zirconium has a low neutron absorption cross-section [7], zirconate pyrochlores have also been proposed as inert matrix materials for actinide burning [7,9] and host matrices for high level radioactive waste, especially for long half-life actinides [10].…”
Section: Introductionmentioning
confidence: 99%
“…Polycrystalline samples of Gd 2 Ti 2 O 7 and La 2 Ti 2 O 7 were synthesized by a sol-gel method, the details of which have been reported elsewhere [21]. The typical grain size of the samples was several microns, and the measured densities of Gd 2 Ti 2 O 7 and La 2 Ti 2 O 7 were 6.56 g/cm 3 and 5.82 g/ cm 3 , respectively.…”
Section: Methodsmentioning
confidence: 99%
“…[31][32][33], and in many other ternary compounds, e.g. CaTiO 3 and A 2 B 2 O 7 compounds [34][35][36][37][38]. Tang et al [31] studied the irradiation response in rare earth sesquioxides and found the phase transformation from cubic phase to the monoclinic phase which is closely related to the temperature.…”
Section: The Formation and Growth Of The Irradiation-induced Fcc Phasementioning
confidence: 97%